Price threshold, discount saturation point and postponement behavior for products and services in Singapore. - Leong, Joyce Tien Mei. (2008)
This research had investigated the effect of advertised discounts and perceived quality on the purchase intention of consumers. In particular, the existence of the “discounting of discounts” phenomena in Singapore is confirmed, as are the threshold and saturation points, and knowledge extended by examining the effect of the branding of both services and products within this price discount context.